2003
DOI: 10.1113/jphysiol.2003.041897
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 24 h Telemetered Blood Pressure in eNOS‐Knockout and C57Bl/6J Control Mice

Abstract: The purpose of the present study was to characterize in detail the 24 h blood pressure (BP) phenotype of mice lacking the gene for endothelial nitric oxide synthase (eNOS_/_) and the corresponding control strain (C57Bl/6J). Twenty-four hour BP recordings were made in conscious 12-to 16-week-old male mice 10 days following the implantation of a BP telemeter (n = 9 per group). The BP and heart rate of both strains were markedly affected by brief locomotor activity cycles, resulting in bimodal distributions of BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
101
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 40 publications
(102 reference statements)
16
101
0
1
Order By: Relevance
“…This suggests that NO causes diurnal fluctuations in medullary oxygenation. NO is involved in the regulation of circadian rhythmicity in blood pressure 28, 29, 30. A shift in peak blood pressure of 4 hours was found in the current study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This suggests that NO causes diurnal fluctuations in medullary oxygenation. NO is involved in the regulation of circadian rhythmicity in blood pressure 28, 29, 30. A shift in peak blood pressure of 4 hours was found in the current study.…”
Section: Discussionsupporting
confidence: 70%
“…Healthy renal pO 2 in cortex and medulla shows circadian rhythmicity 27. NO depletion is known to affect the diurnal rhythm of blood pressure in rodents,28, 29, 30 but effects on renal oxygenation circadian rhythm are as yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The salt‐sensitive BP finding is supported by previous studies wherein global NOS3 KO caused hypertension,16, 17 but re‐expressing vascular endothelial NOS3 in the setting of global NOS3 KO did not normalize BP18 suggesting that non‐endothelial NOS3 modulates BP. Importantly, the hypertension and impaired Na + excretion in NOS3 KO mice was not associated with altered GFR.…”
Section: Discussionsupporting
confidence: 74%
“…1 These results are supported by several studies which have shown a disturbance in circadian rhythms in genetically modified mice (eNOS-knockout mice). 7 The results of our study agree with this work and support the role of eNOS in circadian BP regulation in humans.…”
supporting
confidence: 91%